Direct fabrication of LiCoO2 thin-films in water–ethanol solutions by electrochemical–hydrothermal method. (1st April 2015) - Azib, T.; Le Cras, F.; Porthault, H.
Highlights: LiCoO2 thin films synthesized by electrochemical hydrothermal process. Smoother films with no impurities obtained by using ethanol as co-solvent. Synthesis of the lamellar R-3m LiCoO2 at temperature as low as 125 °C. Good electrochemical performances of synthesized films in liquid electrolyte. Abstract: LiCoO2 thin films were synthesized via an easy one-step electrochemical-hydrothermal route using ethanol–water blends as solvent. The influence of the synthesis parameters - i.e. ethanol/water ratio, temperature, pressure, reaction time and current density - on the formation of layered R 3 ¯ m phase and on its electrochemical behavior in lithium cells was investigated. X-ray diffraction (XRD) shows the formation of well-crystallized R 3 ¯ m LiCoO2 thin films with preferred (1 0 1) orientation, without any trace of spinel-like (LT-LiCoO2 ) phase or cobalt oxide Co3 O4 impurities. LiCoO2 films with controlled orientation exhibit a specific capacity close to the theoretical value, and excellent capacity retention even at high current density. Experimental results reveal that electrodeposition under hydrothermal conditions allows high deposition rates reaching 500 nm min −1 .